Discrimination of healthy controls and selected visually impaired through visually evoked potentials - Vikneswaran Vijean (School of Mechatronic Engineering, University Malaysia Perlis, 2014)
This thesis presents a digital signal processing based detection of healthy controls and selected visually impaired through visually evoked potentials (VEP).